2015
DOI: 10.1007/s13304-015-0312-5
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic major hepatectomies: current trends and indications. A comparison with the open technique

Abstract: Diffusion of laparoscopic major hepatectomies is experiencing a steady increasing trend, although slower compared to minor resections. The aim of this single-center study is to discuss current trends and indications in the application of minimally invasive techniques to major hepatic resections. Preoperative patients and disease characteristics of 49 laparoscopic major hepatectomies (LPS group), performed between 2005 and 2015, were compared with 585 open hepatectomies (Open group) to analyze differences in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…All retrospective studies comparing between the laparoscopic and open approach for major hepatectomies were selected in accordance with the inclusion criteria (n = 13). [12][13][14][15][16][17][18][19][20][21][22][23] As two institutions had published two consecutive articles with duplication of patients, only the most recent article was considered. 10,11 The 11 retained articles had a retrospective design and were published between 2009 and 2017.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All retrospective studies comparing between the laparoscopic and open approach for major hepatectomies were selected in accordance with the inclusion criteria (n = 13). [12][13][14][15][16][17][18][19][20][21][22][23] As two institutions had published two consecutive articles with duplication of patients, only the most recent article was considered. 10,11 The 11 retained articles had a retrospective design and were published between 2009 and 2017.…”
Section: Resultsmentioning
confidence: 99%
“…13,22,23 As such, the eight remaining studies were included in the meta-analysis with IPD (Table 1). [14][15][16][17][18][19][20][21] No disclosure of results from any prospective, randomized, controlled trial was identified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several series reporting procedures involving all liver segments are currently available in the literature and even major hepatectomies and resections of postero‐superior segments are reported , even though with a different profile of difficulty as compared to procedures involving the so‐called “laparoscopic segments”. During the Second International Consensus Conference for Laparoscopic Liver Resection , held in Morioka in 2014, a difficulty index (DI), which is the cumulative score comprising scores for five individual items (lesion size and location, proximity to vessels, extent of hepatectomy and liver function) , was developed in an effort to predict preoperatively the difficulty of procedures, in an assessment and educational perspective.…”
Section: Introductionmentioning
confidence: 99%